THE EVOLUTION OF SPEECH STYLES AND THE FUNCTIONAL–PRAGMATIC DEVELOPMENT OF PUNCTUATION MARKS - Turayeva Dilbar Meyliyevna (Modern American Journals, 2026)
Language is a dynamic and socially conditioned system that constantly evolves in response to communicative needs, cultural shifts, and changes in discourse practices. One of the most evident manifestations of this evolution can be observed in the development of speech styles, which reflect the functional diversification of language in various communicative spheres. As speech styles undergo continuous transformation, the linguistic means employed within them also acquire new functions and semantic nuances. Among these means, punctuation marks occupy a special position, as they function not only as structural indicators of syntactic relations but also as significant carriers of functional and pragmatic meaning. In contemporary linguistics, punctuation is increasingly viewed as an integral component of discourse organization, contributing to the expression of communicative intent, emotional coloring, and stylistic differentiation of texts.